A Conductometric Study of Complexation Reactions Between 4-Nitrobenzo-15-Crown-5 with Ag+, Hg2+, Tl+ and La3+ Metal Ions in Acetonitrile-Methanol Binary Solutions - Boosaeeidi, F.; Rounaghi, G.H.; Kazemi, M.S. (Asian Journal of Chemistry, 2010)
The complex formation between Ag+, Hg2+, Tl+ and La3+ metal ions with macrocyclic ligand, 4-nitrobenzo-15-crown-5 (NB15C5) was studied in acetonitrile (AN)-methanol (MeOH) binary systems at different temperatures using conductometric method. The obtained results show that the stoichiometry of the complexes is 1:1 (ML), but in the case of Hg2+ cation, in addition to a 1:1 complex, a 1:2 (ML2) complex is formed in solutions. The stability constants of the complexes were obtained from fitting of molar conductivity curves using a computer program, Genplot. A non-linear behaviour was observed for changes of log Kf of the complexes versus the composition of AN-MeOH binary solution. The results show that the selectivity of NB15C5 for the metal cations changes with the composition of the mixed solvent. The values of standard enthalpy changes (ΔH°c) for complexation reactions were obtained from the slope of the van't Hoff plots and the changes in standard entropy (ΔS°c) were calculated from the relationship: ΔG°c, 298.15 = ΔH°c - 298.15 ΔS°c. The obtained results show that the complexes are entropy stabilized but from the enthalpy view point, depending on the solvent system the metal ion complexes are stabilized or destabilized and the values of ΔH°c and ΔS°c depend strongly on the nature of the medium.